Sex exploitation in the editorial content of malay magazines after the Second World War, 1945-1957 - Hamedi, M.A. (Medwell Journals, 2016)
The Malay magazine publishing in the period after World War II had a quick progress. The 145 magazines were published at this time with >35% of it were magazines in the form of entertainment and magazines which tend to exploit sex. In a loose meaning, sex in Malay magazines is in the form of photography, particularly the actress or Western model pictures and description on obscene actions. This study discusses editorial elements in the Malay magazine publishing after the Second World War, specifically the ones concerning the exploitation of sex in entertainment magazines. This discussion on the magazine publishing history uses copies of magazines as the main source. In general, it is found out in the study that entertainment magazine publishers have to use sexual elements as the bait for readers. These are elements needed by the audience due to keen competition to vie for readers. Furthermore, while the income from the selling of advertisement spaces in magazines and circulations cannot be guaranteed that the selling of magazines is not interrupted in the market.